(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The issue of measurement of operational efficiency and productivity plays a major role in determining the weakness of the company, especially in relation to the productive processes, and thus starting to address these points and improve their performance. Hence the problem of research on how to determine the constraints in the production process, to identify weaknesses in the company. The research aims to clarify the role of throughput accounting in measuring the operational efficiency of the company in addition to clarify some of the constraints and causes behind them. The study concluded a set of conclusions, the most important of which is the availability of throughput accounting indicators that help in measuring operational efficiency such as (margin of throughput, rate of throughput), which determine the weaknesses of the company and especially what is related to the Production process. The researcher recommends the need to measure the operational efficiency on a continuous basis and the use of several methods and indicators for their role in the detection of weaknesses in the company, and the need to address the constraints discovered in order not to exacerbate the problems in the company, leading to the consumption of resources.